New Campanian kossmaticeratid ammonites from the James Ross Basin, Antarctica, and their possible relationships with Jimboiceras? antarcticum Riccardi - Olivero, Eduardo Bernardo
Field work on James Ross Island, Antarctica, has resulted in the finding of a new upper Campanian ammonite fauna, which in SE James Ross Island includes in stratigraphic succession: a) Neokossmaticeras redondensis gen. et sp. nov., recorded in the upper part of the Rabot Formation, and b) Neograhamites primus sp. nov., Kossmaticeratinae gen. nov., and Baculites delvallei Riccardi, recorded in the basal part of the Hamilton Point Member of the Snow Hill Island Formation. All these species are also recorded in NW James RossIsland as reworked fossils in a single conglomerate bed at the base of the Gamma Member, Snow Hill Island Formation, indicating a marked unconformity between the Santa Marta and Snow Hill Island formations. Kossmaticeratinae gen. nov. is very similar toJimboiceras? antarcticum Riccardi, and thus, the association of J.? antarcticum and B. delvallei, previously known only from a Pleistocene glacial boulder, can be interpreted as upper Campanian and derived from the Hamilton Point Member of the Snow HillIsland Formation. Fil: Olivero, Eduardo Bernardo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina